2019
DOI: 10.5114/ada.2019.89712
|View full text |Cite
|
Sign up to set email alerts
|

Itch in diabetes: a common underestimated problem

Abstract: Introduction: Diabetes mellitus is associated with several skin manifestations, however the association with itch remains unclear. Aim: To present a detailed literature review in order to analyse the frequency, pathogenesis, and course of itch in diabetes mellitus. Material and methods: Data were collected from the PubMed and Cochrane databases. Articles were excluded if the populations presented with comorbidities or received treatment with drugs affecting the skin. Also, animal studies, studies with poor met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…In the present survey, the physicians (CP and endocrinologists) reported the 14% (n = 46) patients with diabetes had pruritus. The results were in accordance with previous published literature, both at the global and regional level where the prevalence of cutaneous manifestations and pruritus in persons living with diabetes have been established [10,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present survey, the physicians (CP and endocrinologists) reported the 14% (n = 46) patients with diabetes had pruritus. The results were in accordance with previous published literature, both at the global and regional level where the prevalence of cutaneous manifestations and pruritus in persons living with diabetes have been established [10,[23][24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…Further, in patients with elevated blood glucose there is an increase of advanced glycosylated products in the collagen of the dermis leading to pruritus [6]. Globally, 18.4-27.5% diabetes patients present with pruritus [8][9][10][11]. An Indian cross-sectional study conducted in a tertiary care hospital, reported that 13.3% of the diabetes patients had pruritus without skin lesions.…”
Section: Survey Methodologymentioning
confidence: 99%
“…However, researchers have recently suggested that the etiology of itch in DM is additionally involved with both dermatologic and neurologic components [ 6 , 7 , 8 ]. The occurrence of itch in DM ranges from 18.4 to 27.5% [ 9 ]; however, the exact prevalence is not known, as most studies used inconsistent definitions and various tools for itch evaluation and included heterogeneous diabetic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers classify itch in diabetes, according to the International Forum for the Study of Itch (IFSI), as systemic itch [9]; however, some authors suggested mixed etiology of diabetic itch with the additional involvement of both dermatologic and neurologic components [10][11][12]. Only a few studies investigated the occurrence of itch in DM, reporting a wide prevalence ranging from 18.4-27.5% [13]. However, these studies used inconsistent definitions and various tools for itch evaluation and included heterogeneous diabetic populations.…”
Section: Introductionmentioning
confidence: 99%